THE LEVEL OF FAMILY WELFARE OF SAND MINERS IN TEBING TINGGI VILLAGE, TEBO TENGAH SUB-DISTRICT, TEBO REGENCY, JAMBI PROVINCE - RAHMAH, ELZI; Juita, Erna; Farida, Farida (STKIP PGRI Sumbar, 2014)
Abstract This aims of study to determine the level of family welfare of sand miners in Tebing tinggi village, Tebo Tengah sub-district, Tebo regency, Jambi province viewed from state revenues, the state of education, the condition of basic needs (food, clothing, housing), and health conditions in the family. This type of research is a descriptive study. Population in this study were all the family sand miners in Tebing tinggi village, Tebo Tengah sub-district, Tebo regency, Jambi provine. The sample of the total population in the region amount as 102 households, while the sampling technique with a total sampling respondents. Research data collection using a questionnaire data analysis techniques using a percentage formula. Results of the study showed that 4 variables: 1). state revenue is still low in view of the sand miners <Rp 400.000/week by 60 respondents (58.83%), 2). the ability of the sand miners families in achieving education was classified as less capable in primary school where most of the answers proved as much in 38 respondents (37.25%) 3). basic needs such as food conditions classified as less capable, while the board and clothing are included welfare, and 4). health in view of the illness suffered last year was as much flu and fever (41.33%).